Hidden Meanings of the Culture War over Abortion in the United States - MAIER, Elizabeth (Frontera Norte, 2018)
This article examines the dispute over abortion in the United States, within a broader context of the transition between the industrial era and the postindustrial, globalized model. My contention is that present clashes over abortion must be considered within this framework, so as to understand them not only as a conflict of values on fundamental issues of life, personhood, citizenship, gender, and family, but also as a contest for the institutional nature of a reconfigured structural and technological order. While the abortion controversy exemplifies contrasting biopolitics, it also represents new tensions over the margins of separation of religion and state.